Comparative Effectiveness of Papaya Leaf Stew (Carica Papaya Linn) With Turmeric Acid (Curcuma Domestica Val-Tamarindus Indica) Against Primary Dysmenorrhea: Perbandingan Efektifitas Rebusan Daun Pepaya (Carica Pepaya Linn) Dengan Kunyit Asam (Curcuma Domestica Val-Tamarindus Indica) Terhadap Dismenore Primer - Liana, Yunita (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Young women often feel primary dysmenorrhoea because the hormonal cycles experienced are not stable, this can disrupt the concentration and activity of young women. The principle of back to nature is increasingly popular today, the side effects of chemical drugs can cause new problems, it is one of the driving force of the development of traditional medicine. Papaya leaves contain Vitamin E which can reduce dysmenorrhea. In addition, turmeric acids also contain curcumine and anthocyanins that inhibit cyclooxygenase, thereby reducing the occurrence of inflammation during uterine contractions. The aim of this research is to know the effectiveness of papaya leaf stew with acidic turmeric to primary dysmenorrhea. Type of Research is an experimental study with a Pretest-Posttest Control Group Design design. The sample is 30 people. The research was conducted on December 27, 2017 s.d February 24, 2018 at SMP Negeri 46 Palembang. Instrument to measure pain Numeric Rating Scale. The statistical test used by Wilcoxon and Mann Whitney U. Average score of pain before papaya leaves stem 5.40 ± 0.73 while the mean score of pain after given turmeric acid 5.33 ± 0.61 The mean score of pain after being given papaya leaves stew 3.60 ± 0.91 while the mean score of pain after given turmeric acid 4.06 ± 0.79. There was a difference of mean score of dysmenorrhea pain before and after given papaya leaf stem p value = 0.000. There is difference of mean score of dysmenorrhea pain before and after given turmeric acid p value = 0,002. There was no difference of mean score of dysmenorrhea pain before and after given papaya leaf sting and turmeric acid p value = 0,217. The decoction of papaya leaf and turmeric acid have the same effectiveness in reducing primary dysmenorrhea pain.